Effect of alcohol use disorder on oxytocin peptide and receptor mRNA expression in human brain: A post-mortem case-control study. (November 2017) - Lee, Mary R.; Schwandt, Melanie L.; Sankar, Vignesh; Suchankova, Petra; Sun, Hui; Leggio, Lorenzo
Highlights: Fold change in oxytocin peptide mRNA levels was significantly elevated in the prefrontal cortex of subjects with alcohol use disorder compared to controls. There was a significant positive correlation for the entire group between fold change in mRNA for oxytocin peptide in the prefrontal cortex and both daily alcohol intake and drinks per week. This is the first human postmortem study to examine the endogenous brain oxytocin system outside of the hypothalamus in subjects with alcohol use disorder. Abstract: Animal and human evidence supports a role for oxytocin in alcohol-seeking behaviors. There is interest, therefore, in targeting the oxytocin pathway as a new pharmacologic approach to treat alcohol use disorder. To this end, it is important to understand the effect of alcohol use disorder on endogenous oxytocin in brain regions that are relevant for the initiation and maintenance of alcohol use disorder. We examined human post-mortem brain tissue from males with alcohol use disorder ( n = 11) compared to nonalcohol dependent male controls ( n = 16). We a priori targeted five brain regions that in rodent studies, are projection areas for oxytocin neurons: nucleus accumbens, amygdala, hippocampus, ventral tegmental area and prefrontal cortex. Fold change in mRNA levels of oxytocin peptide and receptor were measured in each of the brain regions studied. Fold change for oxytocin peptide mRNA was significantly elevated in the prefrontal cortex of subjects with alcohol use disorder compared to controls (uncorrected p = 0.0001; FDR-corrected p = 0.001). For the entire sample of 27 subjects, there was a significant positive correlation between the fold change in oxytocin peptide mRNA in the prefrontal cortex and both daily alcohol intake ( r 2 = 0.38; p = 0.002) and drinks per week ( r 2 = 0.24; p = 0.02). Results are discussed in light of the previous animal and human literature on changes in the endogenous oxytocin system as an effect of chronic alcohol exposure.